How Supply Chain Moderates The Relationship of Entrepreneurial Orientation, Adaptability Strategy and Government Interference with Performance? - Savitri, Enni; Herda Nik Abdullah, Nik; Said, Jamaliah; Syahza, Almasdi; ., Musfialdy (International Journal of Supply Chain Management, 2020)
The small and medium business sector plays an important role in strengthening the structure of the national economy. This sector is essentially related to the economic life of most Indonesian people. Past studies indicate that the quality of small and medium enterprises in Indonesia facing difficulties to extend their businesses due to several internal problems such as lack of human resources entrepreneurial skill, technology, management, and information. As such, based on Resource-Based View theory, this study aims to analyze the effect of adaptability strategy, entrepreneurial orientation, and the government policy on the performance of selected small and medium enterprises. Information sharing wide supply chain management significantly and positively inserts moderating effect among the relationship between government policy, adaptability strategy, entrepreneurial orientation, and performance. Based on interviews and questionnaires distributed to 49 small and medium enterprises, this study found adaptability strategy, entrepreneurial orientation, and the government policy affects business performance. This study enriches the current literature by providing contributions and insights to understanding how Resource-Based View theory will affect the business performance of small and medium enterprises in Indonesia.